Integration and Coordination in the Development of China's Electric Vehicle Industry: Mechanisms and Policy Implications - Yong, Wang; Wan, Xu; Qiyuan, Hu (China economist (Beijing, China), 2024)
Chinas electric vehicle industry has undergone a rapid development over the past decade, boasting cutting-edge technology and a mature domestic market. The growth of China's electric vehicle (EV) industry is prominently characterized by integration and coordination along the industrial supply chain. This paper provides a systematic analyze on China's EV industrial integration and develops a framework to investigate its mechanisms in promoting industrial development. In particular, we explored the crucial role of coordinated integration along the industrial supply chain in leveraging the comparative advantages of each segment and building overall international competitiveness. Finally, pathways and policy recommendations are proposed for promoting the high-quality development of other strategic emerging industries through industrial integration and coordination.